PENGEMBANGAN MEDIA VIDEO ANIMASI PADA MATERI HAK, KEWAJIBAN, DAN ATURAN UNTUK SISWA KELAS IV SEKOLAH DASAR - Maya Erlita; Zaka Hadikusuma Ramadan (STKIP Subang, 2023)
This research is motivated by the lack of variety of educators in the use of learning media such as projectors as learning support tools that are not utilized optimally by educators. This study aims to develop and describe the validity of animated video media on the material rights, obligations, and rules for fourth grade students as basic. Research uses development research with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. In this research, it only reached the development stage. Data collection was carried out through interviews and validation questionnaires. The data analysis techniques used are qualitative data analysis techniques and quantitative data analysis techniques. Qualitative data is obtained from comments or suggestions from validators and quantitative data is obtained from validity scores from validators. The validity of animated video media in the material aspect obtained a percentage of 85.83% in the very valid category, the language aspect obtained a percentage of 87.5% in the very valid category, and the media aspect obtained 90.06% which was included in the very valid category. The final result of the average validity is 87.79% which is included in the very valid category.